Free amino acids in fibromyalgia syndrome: relationship with clinical picture. (17th February 2017) - Ruggiero, Valeria; Mura, Massimiliano; Cacace, Enrico; Era, Benedetta; Peri, Marcella; Sanna, Giuseppina; Fais, Antonella
Abstract: The objectives of our study were to evaluate free amino acid (FAA) concentrations in the serum of patients affected by fibromyalgia syndrome (FMS) and to determine the relationships between FAA levels and FMS clinical parameters. Thus, serum amino acid concentrations were quantified (HPLC analysis) in 23 females with fibromyalgia (according to the American College of Rheumatology classification criteria) and 20 healthy females. The results showed significantly higher serum concentrations of aspartate, cysteine, glutamate, glycine, isoleucine, leucine, methionine, ornithine, phenylalanine, sarcosine, serine, taurine, tyrosine and valine in FMS patients vs. healthy controls. Patients with higher Fibromyalgia Impact Questionnaire (FIQ) scores showed increased levels of alanine, glutamine, isoleucine, leucine, phenylalanine, proline and valine. In conclusion, our results indicate an imbalance in some FAAs in FMS patients. Increased Glu is particularly interesting, as it could explain the deficit in monoaminergic transmission involved in pain.